2020
DOI: 10.1111/jdi.13284
|View full text |Cite
|
Sign up to set email alerts
|

Low urine pH predicts new onset of diabetes mellitus during a 10‐year period in men: BOREAS‐DM1 study

Abstract: Aims/Introduction A low level of urine pH (U‐pH) has been reported to be associated with metabolic disorders. However, the relationship between the incidence of diabetes mellitus and U‐pH has not yet been fully addressed. Materials and Methods We investigated the relationship between U‐pH and the development of diabetes mellitus during a 10‐year period in a general population of individuals who received annual health examinations in 2006 ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
2
16
1
Order By: Relevance
“…The plasma XOR activity levels of type 2 diabetes patients in the current study was higher than reported levels in Japanese general population 14 , 23 . In this study, the plasma XOR activity showed no correlation with the fasting glucose level or percent HbA1c in the patients with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The plasma XOR activity levels of type 2 diabetes patients in the current study was higher than reported levels in Japanese general population 14 , 23 . In this study, the plasma XOR activity showed no correlation with the fasting glucose level or percent HbA1c in the patients with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 84%
“…Since hypoxanthine is a precursor of xanthine, this association between hypoxanthine and xanthine might be easy to conceive. Significant associations between the plasma levels of hypoxanthine and xanthine, and between the plasma xanthine and XOR activity were also reported by another study conducted in the general population 23 . The plasma XOR activity and xanthine levels, but not the plasma hypoxanthine level, were correlated with the BMI, unlike the results of a previous study 23 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A total of 28,990 subjects who received annual medical checkups at Keijinkai Maruyama Clinic, Sapporo, Japan in 2006 were enrolled in this registry 45 , 46 . A flow chart of the study subjects is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All of subjects who received annual health examinations at Keijinkai Maruyama Clinic, Sapporo, Japan in 2006 were enrolled in this registry (n = 28,990) 48 , 49 . A flow chart of the study participants is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%